A Study of Anxiety Symptoms in Children and Adolescents during the COVID-19 Pandemic in Qatar - Mariem Moalla; Shuja Reagu; Majid Alabdulla; Yasser Saeed Khan; Ziad Takish; Tumadher Al-Musfir; Buthaina Al Emadie; Manal Matoug Elwerfellie; Srinivasan Narasimhan; Hani Nazzal (Psychiatry International, 2023)
Background: There is clear evidence showing an increase in mental health symptoms along with an increased demand for mental health services since the start of the COVID-19 pandemic. Objective: This study aimed to determine the rates of elevated anxiety symptoms in children during the COVID-19 pandemic in the state of Qatar. It also explored any correlated factors. Method: A cross-sectional, questionnaire-based study with 199 participants (children aged 6–16 years) consulting a dental care center. We used the original English version as well as a previously validated Arabic version of the Parent Spence Children’s Anxiety Scale to measure anxiety symptoms. Results: A total of 29.6% (n = 59) of our sample met the respective elevated cut-off score for overall anxiety disorder. The largest group among the children was elevated levels of physical injury fears 37.6% (n = 75), followed by Social Phobia 36.1% (n = 72). Younger children showed significantly higher scores for total anxiety, separation anxiety, physical injury fears, and generalized anxiety score. Among the gender groups, females reported significantly higher scores of General anxiety disorder. When comparing natives to expatriates, expatriates showed higher scores for total anxiety, physical injury fears score, social phobia score, and generalized anxiety. Conclusions: Overall, this study shows increased rates of clinically elevated anxiety symptoms in children during the COVID-19 pandemic in the state of Qatar. Younger children, females, and expatriates were more vulnerable to the psychological impact of the COVID-19 pandemic. This study highlights the specific psychological vulnerability of this population group during major health crises like the current pandemic.